2013
DOI: 10.7314/apjcp.2013.14.3.1629
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Univariate and Multivariate Gene Set Analysis in Acute Lymphoblastic Leukemia

Abstract: Background: Gene set analysis (GSA) incorporates biological with statistical knowledge to identify gene sets which are differentially expressed that between two or more phenotypes. Materials and Methods: In this paper gene sets differentially expressed between acute lymphoblastic leukaemia (ALL) with BCR-ABL and those with no observed cytogenetic abnormalities were determined by GSA methods. The BCR-ABL is an abnormal gene found in some people with ALL. Results: gene sets differentially expressed between two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Besides univariate statistics, which considers the effect of a single gene expression, multivariate analysis was conducted to account for the relationship (covariance and correlation) among the expressed genes, making the two approaches, complementary. Indeed, since the transcription levels of genes involved in the same metabolic pathways are often highly correlated, there is a growing trend to analyze gene expression data utilizing both univariate and multivariate approaches [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides univariate statistics, which considers the effect of a single gene expression, multivariate analysis was conducted to account for the relationship (covariance and correlation) among the expressed genes, making the two approaches, complementary. Indeed, since the transcription levels of genes involved in the same metabolic pathways are often highly correlated, there is a growing trend to analyze gene expression data utilizing both univariate and multivariate approaches [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Introduction leukemia (CML) treatment and indicates at an early stage resistance development or disease progression (Ohsaka et al, 2002;Hehlmann et al, 2007;Hunger, 2011;Ohanian et al, 2012;Sabir et al, 2012;Soheila et al, 2013). Recent research showed that BCR-ABL fusion gene can also be detected in 25-30% of adult and 2-5% of childhood cases of acute lymphoblastic leukemia (ALL), and less frequently, in acute myelogenous leukemia (AML) (Den Boer et al, 2009;Uchida et al, 2009;Yeung et al, 2012).…”
mentioning
confidence: 99%
“…For example, Nordlund et al used DGE profiling to characterize the gene expression patterns in different ALL subtypes (20), and found that antisense tags expressed from the non-coding strand were also expressed as a subtype-specific pattern. Additionally, other studies have used microarray-based methods to profile ALL gene expression patterns (10,11,21) However, these previous studies were performed in Western countries, and comparable information in Asian populations is limited. To the best of our knowledge, the present study is the first to use DGE profiling to determine gene expression patterns in childhood ALL in a Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple technologies have been used to identify the differentially expressed genes associated with childhood ALL. For example, gene expression microarray analyses of differentially expressed genes in ALL subtypes (10) have identified 80-300 genes as marker genes, which are necessary for discriminating the subtypes. In addition, sequencing-based methods, including serial analysis of gene expression (SAGE), have been used to measure absolute gene expression levels in ALL subtypes (11).…”
Section: Introductionmentioning
confidence: 99%